IMPLEMENTASI DETEKSI GANGGUAN PERTUMBUHAN PERKEMBANGAN BALITA (USIA 1-5 TAHUN) DENGAN STIMULASI, DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) DI POSYANDU KUCAI KELURAHAN TELUK KABUPATEN BANYUMAS - Rini, Susilo; Wijaya, Amelia Puspita (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: INTERFERENCE DETECTION IMPLEMENTATION GROWTH - DEVELOPMENT TODDLERS ( AGES 1-5 YEARS ) WITH STIMULATION , DETECTION AND EARLY INTERVENTION GROWTH ( SDIDTK ) IN THE BAY VILLAGE KUCAI IHC BANYUMAS. Early detection through SDIDTK is necessary to find the early deviation of growth, mental and emotional development in children. The research was conducted at the IHC Kucai because studies have not been done before using SDIDTK sheet. Objective: To determine Preview Stimulation, Detection and Early Intervention Developmental (SDIDTK) In Toddlers (Age 1-5 Years) at IHC Kucai 2012. Methods: The study was a descriptive cross-sectional quantitative approach. The samples used were Accidental sampling, sample research is Toddlers in IHC Kucai sample in this study 84 Toddler. The research instrument used scales, metlin and SDIDTK sheet. Types of data are primary and secondary data. Analysis of the data used is the univariate analysis. Results: The result showed Stimulation, Detection and Early Intervention on Toddler Growth In IHC Kucai In 2012 most of the growth is normal infants were 44 respondents (83%), normal childhood development by 44 respondents (83%), children do not have a problem emotional mental by 47 respondents (88.7%), respondents had a low risk of autism by 50 respondents (94.3%), do not have attention deficit disorder and hyperactivity by 48 respondents (90.6%). Conclusion: Most of the Stimulation, Detection and Early Intervention Toddler Growth is good. Â Keywords: Â Stimulation, Detection and Early Intervention Developmental, Toddlers (age 1-5 years)